2017
DOI: 10.5551/jat.36517
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship between Sleep Duration and Cardio-Ankle Vascular Index in Children

Abstract: Aim: Poor sleep has been shown to be associated with the development of cardiovascular risk factors, such as obesity, in both adults and children. This study aimed to investigate the relationship between sleep duration and arterial stiffness indices in Japanese children and early adolescents.Methods: The data on 102 students (56 males, 46 females; mean age, 11.9 ± 1.8 years) were analyzed. As non-invasive arterial stiffness parameters, the cardio-ankle vascular index (CAVI) and heart-ankle pulse wave velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…CAVI is significantly higher in shift workers 94) and workers working long overtime hours 95) . There is an inverse relationship between sleep duration and CAVI in children 96) . Interestingly, Shimizu et al 97) reported that people had higher CAVI shortly after experiencing a huge earthquake, even though they were in a hospital situated about 300 km from the epicenter of the earthquake.…”
Section: (A) Mental Stress and Sleep Disturbancementioning
confidence: 92%
“…CAVI is significantly higher in shift workers 94) and workers working long overtime hours 95) . There is an inverse relationship between sleep duration and CAVI in children 96) . Interestingly, Shimizu et al 97) reported that people had higher CAVI shortly after experiencing a huge earthquake, even though they were in a hospital situated about 300 km from the epicenter of the earthquake.…”
Section: (A) Mental Stress and Sleep Disturbancementioning
confidence: 92%
“…In children, there are only few studies on arterial stiffness measured using CAVI. These studies showed increased CAVI in adolescents with essential hypertension compared to healthy controls, positive correlation with age, and an inverse relationship with body mass index (BMI) and sleep duration (Mestanik et al 2016(Mestanik et al , 2017Morita et al 2016;Philip et al 2015). However, the interpretation and clinical application of CAVI as a marker of arterial stiffness in pediatric healthcare is limited due to absence of studies on its sex-and age-specific physiological values during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies linking self-reported sleep duration to arterial stiffness have revealed mixed results. For example, short sleep duration was associated with higher arterial stiffness in middle aged Chinese population with nonalcoholic fatty liver (Cao et al, 2016a), children (Morita et al, 2016), and an elderly population (Zonoozi et al, 2017). On the other hand, several population- based studies have reported associations between long sleep duration and increased arterial stiffness measured by brachial-ankle PWV (baPWV) in middle aged Japanese civil servants (Yoshioka et al, 2011b), Taiwanese males (Tsai et al, 2014b) and elderly in Japan (Niijima et al, 2016).…”
Section: Discussionmentioning
confidence: 99%